4x/3(2x-4)=48

Simple and best practice solution for 4x/3(2x-4)=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x/3(2x-4)=48 equation:


x in (-oo:+oo)

((4*x)/3)*(2*x-4) = 48 // - 48

((4*x)/3)*(2*x-4)-48 = 0

4/3*x*(2*x-4)-48 = 0

4/3*x*(2*x-4)-48 = 0

8/3*x^2-16/3*x-48 = 0

8/3*x^2-16/3*x-48 = 0

8*(1/3*x^2-2/3*x-6) = 0

1/3*x^2-2/3*x-6 = 0

DELTA = (-2/3)^2-(-6*1/3*4)

DELTA = 76/9

DELTA > 0

x = ((76/9)^(1/2)+2/3)/(1/3*2) or x = (2/3-(76/9)^(1/2))/(1/3*2)

x = 3/2*((76/9)^(1/2)+2/3) or x = 3/2*(2/3-(76/9)^(1/2))

8*(x-3/2*(2/3-(76/9)^(1/2)))*(x-3/2*((76/9)^(1/2)+2/3)) = 0

8*(x-3/2*(2/3-(76/9)^(1/2)))*(x-3/2*((76/9)^(1/2)+2/3)) = 0

( x-3/2*((76/9)^(1/2)+2/3) )

x-3/2*((76/9)^(1/2)+2/3) = 0 // + -3/2*((76/9)^(1/2)+2/3)

x = -(-3/2*((76/9)^(1/2)+2/3))

x = 3/2*((76/9)^(1/2)+2/3)

( x-3/2*(2/3-(76/9)^(1/2)) )

x-3/2*(2/3-(76/9)^(1/2)) = 0 // + -3/2*(2/3-(76/9)^(1/2))

x = -(-3/2*(2/3-(76/9)^(1/2)))

x = 3/2*(2/3-(76/9)^(1/2))

x in { 3/2*((76/9)^(1/2)+2/3), 3/2*(2/3-(76/9)^(1/2)) }

See similar equations:

| 3x-37=14 | | 1/2(12p+9)-(p-4) | | 3v+29=5v+7 | | 7x+6=26 | | 23-6x=-37 | | 2x+4(10-x)=28 | | -5x+2=-4(2y+4) | | 8n+62=13n+2 | | -7x-34=64 | | -9/4+8 | | 3x+12=93-6 | | -6x-16=-82 | | c+25=3c+1 | | -11+4x=19+2x | | 3/4*-3 | | -36-5=9-10x | | 90-7x= | | 9x-5(x-12)=30 | | 3/4*3 | | 3x+22=12x-58 | | 3x-8=x-8 | | 110-12x=266 | | 8x+9a-7b+9b-3a+12x= | | (7x+33)=(11x+21) | | 6x+35=15x-35 | | -31-3x=-73 | | x/9-x/10=11 | | 4x-3=14-73 | | 56-11x=166 | | -5=4+x | | -15-4x=45 | | 2n+109=12n-1 |

Equations solver categories